An Evaluation of Three Ways of Communicating Carrier Status Results to the Parents of Children in a Neonatal Sickle Cell Screening Programme - Rémus, Christelle; Stanislas, Aurélie; Bouazza, Naïm; Gauthereau, Valérie; Polak, Michel; Blanche, Stéphane; Niakaté, Assa; Gluckman, Eliane; Tréluyer, Jean-Marc; Munnich, Arnold; Girot, Robert; Cavazzana, Marina (Frontiers in Pediatrics, 2020)
Aim: Sickle cell disease (SCD) is the most frequent monogenic disease worldwide; approximately 5-7% of the world population carry a haemoglobin disorder trait. In the US, one in every 1,941 newborns has SCD, whereas one in every 3000 newborns in France is affected - resulting in 385 new cases and 5883 newly identified carriers per year. The objective of the present study was to evaluate three different ways of providing information to parents at risk of having a child with SCD, with a view to increasing the parental screening rate and decreasing the number of new cases per year in France. Method: In a randomized study, we contacted 300 couples of parents after their child had been identified as a SCD carrier in the French national newborn screening programme: 100 couples received an information letter (the standard procedure in France: arm A), 100 couples received a letter and then a follow-up phone call (arm B), and 100 received a letter and then three follow-up text messages at 5-day intervals (arm C). The primary endpoint was the number of parents in each arm screened in the 120 days after the letter had been sent. In a modified intention-to-treat analysis, the screening rate was 17% in arm A, 35% in arm B, and 30% in arm C. Results: Telephone and text message follow-ups were associated with higher screening rates, compared with no follow-up. After being informed of their child’s carrier status, some parents had consulted a healthcare professional but had not been referred for screening (16% in arm A, 19% in arm B, and 13% in arm C). Conclusion: A letter followed by a phone call or three text messages is more effective than a letter alone for informing parents at risk of having a child with SCD. The effective implementation of this follow-up programme probably requires better training of all the healthcare professionals involved.